Answer:
Your answer is D
Explanation:
Let's solve your system by substitution.
y−2x=3;3x−2y=5
Rewrite equations:
−2x+y=3;3x−2y=5
Step: Solve−2x+y=3for y:
−2x+y=3
−2x+y+2x=3+2x(Add 2x to both sides)
y=2x+3
Step: Substitute2x+3foryin3x−2y=5:
3x−2y=5
3x−2(2x+3)=5
−x−6=5(Simplify both sides of the equation)
−x−6+6=5+6(Add 6 to both sides)
−x=11
−x
−1
=
11
−1
(Divide both sides by -1)
x=−11
Step: Substitute−11forxiny=2x+3:
y=2x+3
y=(2)(−11)+3
y=−19(Simplify both sides of the equation)
Answer:
x=−11 and y=−19